Performance of 3D printed porous polyetheretherketone composite scaffolds combined with nano-hydroxyapatite/carbon fiber in bone tissue engineering: a biological evaluation - Mi, Lian; Li, Feng; Xu, Dian; Liu, Jian; Li, Jian; Zhong, Lingmei; Liu, Yanshan; Bai, Na (Frontiers in Bioengineering and Biotechnology, 2024)
Polyetheretherketone (PEEK) has been one of the most promising materials in bone tissue engineering in recent years, with characteristics such as biosafety, corrosion resistance, and wear resistance. However, the weak bioactivity of PEEK leads to its poor integration with bone tissues, restricting its application in biomedical fields. This research effectively fabricated composite porous scaffolds using a combination of PEEK, nano-hydroxyapatite (nHA), and carbon fiber (CF) by the process of fused deposition molding (FDM). The experimental study aimed to assess the impact of varying concentrations of nHA and CF on the biological performance of scaffolds. The incorporation of 10% CF has been shown to enhance the overall mechanical characteristics of composite PEEK scaffolds, including increased tensile strength and improved mechanical strength. Additionally, the addition of 20% nHA resulted in a significant increase in the surface roughness of the scaffolds. The high hydrophilicity of the PEEK composite scaffolds facilitated the in vitro inoculation of MC3T3-E1 cells. The findings of the study demonstrated that the inclusion of 20% nHA and 10% CF in the scaffolds resulted in improved cell attachment and proliferation compared to other scaffolds. This suggests that the incorporation of 20% nHA and 10% CF positively influenced the properties of the scaffolds, potentially facilitating bone regeneration. In vitro biocompatibility experiments showed that PEEK composite scaffolds have good biosafety. The investigation on osteoblast differentiation revealed that the intensity of calcium nodule staining intensified, along with an increase in the expression of osteoblast transcription factors and alkaline phosphatase activities. These findings suggest that scaffolds containing 20% nHA and 10% CF have favorable properties for bone induction. Hence, the integration of porous PEEK composite scaffolds with nHA and CF presents a promising avenue for the restoration of bone defects using materials in the field of bone tissue engineering.